An improved HPLC method for determination of colocynthin in colocynth - M. Shekarchi; F. Ramezany; M. R. Shams Ardekani; M. Lamshöft; H. Rastegar; M. Eftekhari; M. Khanavi (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Colocynthin is the major active secondary metabolite of colocynth, Citrullus colocynthis (L.) Schrad, which has been used in traditional and ethno medicine of many countries.  It could be considered as an active marker for quality control of colocynth and its herbal products. Analysis and standardization of colocynth and its herbal preparations are a critical issue for their safe applications in phytotherapy and traditional medicine. In the present work, a simple and efficient sample preparation was developed and optimized through combination of matrix solid phase dispersion and ultrasonic assisted extraction. In addition, analytical reversed-phase HPLC method was optimized for analyzing the concentration of colocynthin in colocynth pulp. Methods: Powdered colocynth pulp was grinded with diatomaceous earth to obtain a homogenous mixture. The blend was mixed with methanol and extracted by sonication, followed by centrifugation and filtration. The analytical chromatographic separation was carried out using Luna C18 in isocratic elution with methanol: isopropanol: water: triflouroacetic acid (30:10:60:0.1 v/v). The method was validated as well.  Results: The validation parameters were determines as follows, linear range (r2 = 0.999, 75-500 μg/mL), precision (intra-day < 2.7%, inter-day = 4.4%) and accuracy measured via determination of recovery (90-107%). The limit of detection and quantization were calculated 8.5 and 25.7 μg/mL, respectively. Conclusion: Regarding the relatively high content of colocynthin in colocynth pulp, the validated HPLC method could be applied for quality control of colocynth pulp used in Traditional Persian Medicine.